Intraoperative protective mechanical ventilation in patients requiring emergency abdominal surgery: the multicentre prospective randomised IMPROVE-2 study protocol - Samir Jaber; Emmanuel Futier; Karim Asehnoune; Bruno Pereira; Gerald Chanques; Justine Bourdier; Thomas Godet; Louisa Khaled; Lynda Araujo (BMJ Open)
Methods and analysis The IMPROVE-2 study is a multicentre randomised, parallel-group clinical trial of 680 patients requiring emergency abdominal surgery under general anaesthesia. Patients will be randomly allocated in a 1:1 ratio to receive either low PEEP levels (≤5 cm H2O) without RM or high PEEP levels individually adjusted according to driving pressure in addition to RM, stratified by centre and according to the presence of shock and hypoxaemia at randomisation. The primary endpoint is a composite of PRF and all-cause mortality by day 30 or hospital discharge. Data will be analysed on the intention-to-treat principle and a per-protocol basis.Ethics and dissemination IMPROVE-2 trial has been approved by an independent ethics committee for all study centres. Participant recruitment began in February 2021. Results will be submitted for publication in international peer-reviewed journals.Trial registration number NCT03987789.